Kidney Shear Wave Speed Values in Subjects with and without Renal Pathology and Inter-Operator Reproducibility of Acoustic Radiation Force Impulse Elastography - Bob, Flaviu; Bota, Simona; Sporea, Ioan; Sirli, Roxana; Petrica, Ligia; Schiller, Adalbert (PloS one, 2014)
to assess the inter-operator reproducibility of kidney shear wave speed, evaluated by means of Acoustic Radiation Force Impulse (ARFI) elastography, and the factors which influence it. Our prospective pilot study included 107 subjects with or without kidney pathology in which kidney shear wave speed was evaluated by means of ARFI elastography. Intraclass correlation coefficient (ICC) was used to assess ARFI elastography reproducibility. A strong agreement was obtained between kidney shear wave speed measurements obtained by the two operators: ICC = 0.71 (right kidney) and 0.69 (left kidney). Smaller ICCs were obtained in "healthy subjects", as compared to patients with kidney diseases (0.68 vs. 0.75), in women as compared with men (0.59 vs. 0.78), in subjects younger than 50 years as compared with those aged at least 50 years (0.63 vs. 0.71), in obese as compared with normal weight and overweight subjects (0.36 vs. 0.66 and 0.78) and in case of measurements depth 6 cm as compared with those performed at a depth of 4-6 cm from the skin (0.32 and 0.60 vs. 0.81). ARFI elastography is a reproducible method for kidney shear wave speed assessment.